Students’ Conceptual Understanding and Self-Directed Learning on Blended Learning - Novita, Ria Riski; Jumadi (Journal of Education Technology, 2022)
Learning physics requires understanding the concept so that students can analyze the relationship between concepts to explain a natural phenomenon. However, students need clarification and help to understand and analyze physics concepts. So to train to understand, students need self-directed learning. This study aims to analyze students' conceptual understanding, learning independence, and the effect of student learning independence on students' conceptual understanding of straight motion in blended learning. The sample in this study was 22 students of class X. The method in this study was a pre-experimental design with a one-group pretest-posttest group design. The instrument used in data collection is a test. Data were analyzed using the non-parametric Wilcoxon test and the one-sample T-test. The study results show that blended learning can significantly improve students' conceptual comprehension abilities and learning independence in straight-motion material. It is because students can learn independently during the learning process, so they are more active, creative, and independent in understanding a concept. Learning with blended learning influences understanding concepts, and understanding concepts affects students' self-directed learning.